Distance learning: opportunities and challenges in quarantine. - V. F. Zavizion; I. M. Bondarenko; D. I. Avierin; M. I. Hojouj; N. O. Davlietova; N. O. Cherednychenlo; A. V. Prokhach; V. E. Mashtaler; K. O. Dmytrenko; V. V. Lohvynenko; V. S. Kyslytsyna; O. A. Sukhoversha; et al. (Medičnì Perspektivi)
The urgent introduction of distance education into the learning process due to the COVID-19 pandemic has become a spontaneous experiment, requiring urgent decisions, effective mechanisms to implement into the educational process and analysis of ongoing educational process. The possibilities of modern digital technologies made it possible to quickly set up the information component of education and to controle student’s knowledge. A detailed analysis of the communication between the faculty members of the department among themselves and analysis of the features of teaching and self-education of students in the field of medical radiology and oncology based on answers and comments with using Google classroom, Socrative, Messenger Telegram, etc. was made. Issues of communicative interaction between faculty members and students, psychological aspects of distance communication, language of instruction, logistics of distance education and methodological problems are described in details. It has been suggested that distance education may be equally effective for theoretical subjects in full-time study form, but when studying clinical disciplines, the priority should be given to traditional methods of teaching, involving student's bedside training. Taking into account technical possibilities and high risk of development of extreme and emergency situations, it is suggested to introduce permanent readiness for distance education, to create all – Ukrainian distance imitation service of patients’ follow-up. The importance of using the state language in training as the basis for mastering the professional Ukrainian and English language as the basis for mastering international medical experience is indicated.